Pencak Silat as a Manifestation of Martial Art in the Majapahit Era - Rif'iy Qomarrullah; Fredrik Sokoy (Warisan: Journal of History and Cultural Heritage, 2024)
This article investigates the role of Pencak Silat as a martial art during the Majapahit Empire, emphasizing its dual significance in warfare and the shaping of cultural identity. The research highlights how Pencak Silat was utilized both as a military strategy and a spiritual practice, contributing to the empire's dominance in the Indonesian archipelago. By integrating combat techniques with philosophical values, Pencak Silat became a key factor in Majapahit’s military success. This study adopts a qualitative approach, utilizing primary sources such as epigraphy, historical texts, and cultural artifacts, in addition to secondary literature, to offer a comprehensive analysis. The research also includes visual documentation, such as illustrations of martial arts practices during the era. The findings reveal that Pencak Silat played a pivotal role not only in defending the empire but also in instilling loyalty, discipline, and spiritual resilience among its warriors. Furthermore, the study explores the broader social context of the Majapahit era, differentiating it from other Southeast Asian societies. The article concludes that Pencak Silat had enduring cultural and military importance, leaving a lasting legacy that influenced subsequent generations in the region.